Depressive symptoms in child caregivers of very old Mexican Americans. (2nd January 2021) - Flores, David V.; Rote, Sunshine; Angel, Jacqueline; Chen, Nai-Wei; Downer, Brian; Markides, Kyriakos
Abstract: Objective: To study the effects of disability, cognitive impairment, and neuropsychiatric disturbance among older Mexican Americans on depressive symptoms in their children caregivers. Methods: This study utilizes data from Wave 7 (2010-2011) of the Hispanic Established Populations for the Epidemiologic Study of the Elderly (HEPESE). The final sample included 200 adult children caregivers that provided direct personal care with activities of daily living (ADL) (e.g. bathing, toileting, dressing, etc.) to their older parents (average age = 87). We analyzed the influence of ADL disability, cognition (MMSE), and neuropsychiatric symptoms (NPI) of the care recipient on depressive symptoms of the adult child caregiver. A cross-sectional multivariable linear regression analysis was conducted to examine the effect of neuropsychiatric disturbance on caregiver depressive symptoms. Results: Presence of care recipient NPI symptoms was associated with higher depressive symptoms for caregivers. Additional characteristics associated with caregiver depressive symptoms were not being married, and higher perceived social stress. ADL disability of the care recipient, cognitive functioning of the care recipient, or caregiver health status alone did not have a significant effect on depressive symptoms of the caregiver. Conclusions: In a Mexican American familistic culture, disability and cognitive impairment might be better tolerated by families but neuropsychiatric behavioral symptoms related to dementia may take an increased toll on family member caregivers. The need to provide respite services, mental health resources and community services for caregivers of care recipients with neuropsychiatric symptoms is of paramount importance to alleviate depressive symptoms and burden among caregivers.